Reklamasi Dan Ketahanan Pangan Dari Laut Kabupaten Serang - Arafah, Widiatul; Rizki, Muhammad (Universitas Sultan Ageng Tirtayasa, 2023)
The problem of reclamation in Kramatwatu, Bojonegara, and Pulo Ampel sub-districts is an action that can result in food security not being realized. The problem of reclamation in Kramatwatu, Bojonegara, and Pulo Ampel sub-districts is an action that can result in food security not being realized. The purpose of this study was to analyze the implications of coastal reclamation for food security in the fisheries sector according to Law Number 18 of 2012 concerning Food and to analyze the targets for food security in the fisheries sector in Serang Regency achieved by the existence of the Food Security and Fisheries Service. The method used in this researchis normative juridical and sociological juridical, with analytical descriptive research type. Collection of research data from secondary data which is the main data source in research, and primary data as a source of supporting data in the form of interviews with the Head of the Food Sector of the Food Security and Fisheries Service of Serang Regency. Analyzed qualitatively normative. The result of the research is that the issuance of reclamation permits that conflict with the welfare of coastal communities in the Pulo Ampel, Kramatwatu, and Bojonegara Districts has an impact on not fulfilling the availability of fish. not in accordance with the mandate in Article 12 paragraph (2) and paragraph (4) of Law Number 18 of 2012 concerning Food which states that the government and regional governments are responsible for the availability of food in the region. The consequences of reclamation greatly affect fish production and catches of fishermen. This means that the Serang Regency Food and Fisheries Service has not achieved food security targets in the sub-districts that were fully affected by the reclamation. The problem of food security should be taken seriously. So that synergy is needed between policies and laws and regulations.